The cloning and expression of the two types of kisspeptin gene in hard-lipped barb (Osteochilus vittatus) - NORMAN ARIE PRAYOGO; SAFITRI CITRA RAHAYU; PUTRI PRAHASTUTI AYU SUGITO; SRI BAYUN MEYANADEWI; PURNAMA SUKARDI; RITA EKA ROSITA; YASUMASA BESSHO (Society for Indonesian Biodiversity, 2023)
Abstract. Prayogo NA, Rahayu SC, Sugito PPA, Meyanadewi SB, Sukardi P, Rositas RE, Bessho Y. 2023. The cloning and expression of the two types of kisspeptin gene in hard-lipped barb (Osteochilus vittatus). Biodiversitas 24: 2797-2804. Hard-lipped barb (Osteochillus vittatus Valenciennes, 1842) is a native Indonesian species with many benefits for economic, aquaculture, and environmental sustainability. Several studies showed that the species had high reproductive potential, with kisspeptin gene playing a role in reproductive hormone production and GnRH secretion. Kisspetin gene is also important for gonad maturation in fish. Therefore, this study aimed to determine the structure of Kiss-1 and Kiss-2 genes, as well as the expression of the kisspeptin gene in the hypothalamus and gonads in each phase of female hard-lipped barb development.The study procedure involved several stages, including organ preparation, isolation, sequence identification, and measurement of cGnRH gene expression. The structure of Kiss-1 gene in hard-lipped barb was obtained, and the nucleotide sequence had a product length of 213, coding for 89 amino acids. Meanwhile, Kiss-2 consisted of 230 nucleotides, coding for 76 amino acids, and the sequences observed had 70-80% with other fish species. The results showed that the expression values of Kiss-1 and Kiss-2 genes in the hypothalamus were higher compared to the gonads, with the lowest in the adult phase and the highest in the Juvenile phase. This information will lead us to use the kisspeptin gene to increase hard-lipped barb reproduction.